PROMOSI PARIWISATA BUDAYA NTB MELALUI BERITA PAWANG HUJAN MOTOGP MANDALIKA DI MEDIA SOSIAL - Kariana, I Nengah Putra; Widaswara, Rieka Yulita; Pancawati, Ni Luh Putu Anom (Institut Agama Hindu Negeri Gde Puda Mataram, 2022)
The MotoGP international event has just finished being held at the Mandalika International Circuit, Central Lombok, West Nusa Tenggara. One of the interesting things that was widely reported by media journalists, both national and international media, was the action of rain handler Rara Istiani Wulandri who managed to calm the rain during the MotoGP final race, which was previously hit by heavy rain. The news about the rain handler made NTB viral in the world, especially with regard to local wisdom or tradition, namely the rain handler. This paper aims to find out how the reporting of the Mandalika MotoGP rain handler on social media is a promotion for NTB tourism, especially cultural tourism. The official MotoGP Twitter account is one of the social media that posts news about ritual actions carried out by rain handlers and gets thousands of feedback comments from both Indonesian and foreign followers, this has become a promotion for NTB tourism, especially cultural tourism. The existence of a rain handler as a tradition of local wisdom in an international event that is dominated by modern nuances certainly makes its own value in terms of tourism promotion, especially cultural tourism in NTB, so that people, in this case both domestic and foreign tourists, know that NTB has one of its own. a cultural tradition that can be a tourist attraction.